Project Risk Management for the Repair and Upgrade of Nhi Thien Duong 1 Bridge, Ho Chi Minh City, Vietnam - Huu Hung , Nguyen; Van Hoa, Tran Vu; Huy Viet, Dang; Anh Tien, Luong (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
No project is without risks, especially in the construction industry, which harbors numerous potential pitfalls. Some risks may occur with a low probability but can have a significant impact, while others may manifest repeatedly across various projects. Negative risks, when realized, result in losses that affect the project's objectives. Meanwhile, project participants aspire to capitalize on opportunities presented by positive risks. Therefore, identifying risks, elucidating risk management methods, and formulating risk response strategies for construction projects are crucial to ensure their success. Through methods such as analysis, synthesis, comparison, and reference, this article identifies risks associated with the repair and upgrade project of the Nhi Thien Duong 1 Bridge in Ho Chi Minh City. Additionally, it proposes a set of risk response solutions from the investor's perspective in terms of construction investment management.
Keywords: Risk Management; Risks; Nhi Thien Duong 1 Bridge; Solutions; Strategy